ANALISIS PENGENDALIAN PERSEDIAAN DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) UNTUK MEMINIMALISASI BIAYA PERSEDIAAN PADA UD. MELATI JAYA - Khairunnisa Almadany; Imamati Zikra Ar Rusyfa; Ricka Wahyuni (Institut Pendidikan Tapanuli Selatan, 2020)
The research discusses how inventory control using The Economic Order Quantity (EOQ) Method to minimize inventory costs at UD. Melati Jaya. The Purpose of this research is to find out how inventory control using the EOQ method. The data analisysis method used is quantitative descriptive method. From the result of the research obtained, it is explained that the results of the calculation of the EOQ method are very effective in minimizing the costs of invetory issued by UD. Melati Jaya., that is, with inventory requirements in January 73.993 kg can be minimized with an optimal purchase amount of 16.058 kg with frequency of purchase 5 times a month and procurement of safety stock of 2.963 kg and reorder point when the stock is 8.650 kg. the cost of inventory that can be saved is Rp. 17.504.704. But in the accounting records of UD. Melati Jaya in February to March 2020 is still not good so there are some unrecorded transactions so that the result of calculation of the EOQ method from February to March 2020 have not been efficient. Therefore, It is expected that UD. Melati Jaya is able to improve the quality of control over transactions that occur.